Функціональні поліноми Ерміта в просторі Q[0,1] - Макаров, В.Л.; Хлобистов, В.В.; Демків, І.І. (Видавничий дім "Академперіодика" НАН України, 2007)
In the space of piecewise continuous functions, the Hermite formula with continual knots is constructed on the basis of a Newton-type formula with the use of multiple knots. In this case, the directions of differentiations in interpolation formulas can be arbitrary.